Pengaruh Sajian Program Berita Tatv Terhadap Kebijakan Pemkot Surakarta Dalam Memilih Media Publikasi - Amelia, Citra Ratna; Sugihartono, Ranang Agung (Seni Media Rekam ISI Surakarta, 2011)
TATV is local television pioneer in Surakarta which has tried to present programs thatare beneficial and interesting for the community. Its existence provides an alternativeoption for the Local Government of Surakarta (Pemerintah Kota Surakarta) in the useof mass media as media publications, especially TATV news programs. This study aimedto assess whether TATV news programs affect to policies of the Local Government ofSurakarta in the prioritization of the use of the mass media as a means of publicationor not. This study was a qualitative descriptive research and the data analysis used theinteractive model. From the research that has been conducted showing that the newsprograms â€œFokus Kitaâ€ in TATV can affect to policy of the Local Government of Surakartain terms of the changing in percentage in the use of mass media and changing in the useof funds allocation for the mass media as a means of publication.